2015
DOI: 10.1186/s12889-015-2129-z
|View full text |Cite
|
Sign up to set email alerts
|

Improving child survival through a district management strengthening and community empowerment intervention: early implementation experiences from Uganda

Abstract: BackgroundThe Community and District Empowerment for Scale-up (CODES) project pioneered the implementation of a comprehensive district management and community empowerment intervention in five districts in Uganda. In order to improve effective coverage and quality of child survival interventions CODES combines UNICEF tools designed to systematize priority setting, allocation of resources and problem solving with Community dialogues based on Citizen Report Cards and U-Reports used to engage and empower communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(65 citation statements)
references
References 23 publications
2
62
0
Order By: Relevance
“…Contextual factors such as described in the present study are more likely to be somewhat found at the local level in several low-and middle income countries, as reported in existing literature from Benin [23, 51], Burundi [48], Uganda [58], Tanzania [60] and India [26, 44]. This highlights that the conceptual model as adapted can be used in other setting in order to generate information about local contexts.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Contextual factors such as described in the present study are more likely to be somewhat found at the local level in several low-and middle income countries, as reported in existing literature from Benin [23, 51], Burundi [48], Uganda [58], Tanzania [60] and India [26, 44]. This highlights that the conceptual model as adapted can be used in other setting in order to generate information about local contexts.…”
Section: Discussionsupporting
confidence: 61%
“…They would then be involved in defining, implementing, monitoring, and evaluating health activities. Some examples of successful capacity-building interventions in local settings using participative approaches are provided by Swaans et al(2008) in South Africa [57], Björkman and Svensson (2009) in Uganda [53], Katahoire et al (2015) in Kenya [58], and Manandhar et al (2004) in Nepal [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Given the concerns of some community leaders regarding sustainability of the interventions beyond the funded period, CUAMM (the implementing non-governmental organisation (NGO)) initiated dialogues with the district local government, health authorities and community leaders to explore ways of mitigating some of the potential untoward effects of the interventions 14. Furthermore, the organisation commissioned a study to investigate the feasibility of setting up a community health insurance scheme that could support the transport voucher scheme in the district 35…”
Section: Discussionmentioning
confidence: 99%
“…Interventions designed with inputs from the beneficiary communities are more likely to succeed. Early dialogues involving beneficiary communities before and during the design and implementation of interventions may identify and prioritise the needs of the communities, explore and address potential barriers, and promote community engagement, which may generate a sense of ownership among the beneficiaries 12–14…”
Section: Introductionmentioning
confidence: 99%
“…[10] Because the health system has inadequate financing, management, infrastructure and resources, external agencies such as universities, non-governmental organizations and other donor or development agencies often implement interventions to fill existing gaps. [11] Makerere University College of Health Sciences – School of Public Health (MakCHS-SPH) is one such external agency within the country. To strengthen the health system at district level, a research team (at MakCHS-SPH), in collaboration with three local districts in Eastern Uganda, used the PAR approach to design and implement a maternal and neonatal health project.…”
Section: Introductionmentioning
confidence: 99%